2017
DOI: 10.1099/mgen.0.000120
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and genomic diversification of a virulent serogroup W:ST-2881(CC175) Neisseria meningitidis clone in the African meningitis belt

Abstract: Countries of the African ‘meningitis belt’ are susceptible to meningococcal meningitis outbreaks. While in the past major epidemics have been primarily caused by serogroup A meningococci, W strains are currently responsible for most of the cases. After an epidemic in Mecca in 2000, W:ST-11 strains have caused many outbreaks worldwide. An unrelated W:ST-2881 clone was described for the first time in 2002, with the first meningitis cases caused by these bacteria reported in 2003. Here we describe results of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…(A) Long-term carriage of 5 to 6 months; (B) short-term carriage of 1 to 3 months; (C) carriers where only mutation and HGT has been assessed. spots of recombination and variation in capsule biosynthesis, pilin-associated, pgl, and OMP-encoding genes have been reported in several comparative population studies of meningococcal isolates (34,35,(37)(38)(39). Major changes in antigenic epitopes during persistent carriage are presumed to facilitate evasion of a polyclonal immune response against surface antigens (40)(41)(42).…”
Section: Figmentioning
confidence: 99%
“…(A) Long-term carriage of 5 to 6 months; (B) short-term carriage of 1 to 3 months; (C) carriers where only mutation and HGT has been assessed. spots of recombination and variation in capsule biosynthesis, pilin-associated, pgl, and OMP-encoding genes have been reported in several comparative population studies of meningococcal isolates (34,35,(37)(38)(39). Major changes in antigenic epitopes during persistent carriage are presumed to facilitate evasion of a polyclonal immune response against surface antigens (40)(41)(42).…”
Section: Figmentioning
confidence: 99%
“…This workflow, named by us after the read mapping tool that is used in this workflow, has been applied previously in slightly different configurations for subtyping of various bacterial species including N. meningitidis (Croucher et al, 2011;Lamelas et al, 2014Lamelas et al, , 2017Sater et al, 2015;Kwong et al, 2016;Mentasti et al, 2017;Hao et al, 2018). In the current version which is similar to the one used by Sater et al (2015) and Lamelas et al (2017), reads were mapped at default parameters using SMALT 0.7.6, SNP calling was performed using Samtools 1.8 (Li et al, 2009) and SNP filtering was carried out with Bcftools 1.8 (Li, 2011) retaining positions with a minimal quality of 30, a minimal allele frequency of 75% and a minimal depth of 5 reads. Unless otherwise specified, the Pacbio assembly was used as a reference genome.…”
Section: Smalt-based Pipeline: Smaltpplmentioning
confidence: 99%
“…In the majority of the studies, subtyping of N. meningitidis is being carried out using a wellestablished cgMLST scheme, developed by Jolley et al (2018). Recently, a number of works have also applied assembly-, kmerand mapping-based SNP approaches in some cases combined with recombination detection tools, for characterization of N. meningitidis (Figure 1) (Lamelas et al, 2014(Lamelas et al, , 2017Mustapha et al, 2015;Sater et al, 2015;Stefanelli et al, 2016;Bårnes et al, 2017;Diallo et al, 2017;Tzeng et al, 2017;Hao et al, 2018;Whaley et al, 2018). However, it is not always that clear which method is the best to use for a given research question Whaley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…20 More recently, meningococcal whole genome sequencing has enabled more precise classification of major hypervirulent clonal complexes into distinct sub-lineages. [21][22][23][24][25] Meningococcal pharyngeal carriage is a pre-requisite to infection and asymptomatic carriers are the primary driving force for meningococcal transmission. 14,26 Carriage surveys complement regular invasive disease surveillance by providing data on the extent of spread of known hypervirulent lineages and are an important indicator of herd protection from conjugate vaccines.…”
Section: Neisseria Meningitidismentioning
confidence: 99%
“…62,67,70 Since 2002, a small number of NmW cases associated with the ST-2881 lineage (cc175) were linked to endemic cases but not large epidemics. 23,47 Genomic data from a longitudinal study of meningococcal carriage and disease demonstrated that cc175 strains were genetically similar to NmY strains and may have evolved through Y to W capsular switching, unrelated to cc11 lineage. 23 In addition, only two out of seven ST-2881 sublineages were associated with invasive disease.…”
Section: Capsular Group W Imdmentioning
confidence: 99%